Democratic Republic of the Congo Impacts of the Ukraine and Global Crisis on Food Systems and Poverty: Updated 2022-07-22 - Diao, Xinshen; Dorosh, Paul; Pauw, Karl; Randriamamonjy, Josee; Thurlow, James; Ulimwengu, John M. (2022)
Presentation prepared by Xinshen Diao, Paul Dorosh, Karl Pauw, Josee Randriamamonjy, James Thurlow, and John Ulimwengu, all with the International Food Policy Research Institute, Washington, DC. This is part of the Global Crisis Country Series.